How does labour market structure affect the response of economies to shocks? - Aurelijus Dabušinskas; István Kónya; Stephen Millard (Hungarian Academy of Sciences, Institute of Economics, 2015)
The recent crisis in the Eurozone has led to much discussion about the structure of labour markets in different Eurozone economies. In particular, there has been much talk of the need for structural labour market reform in the Eurozone periphery. But, there are many aspects of labour market structure - eg, wage flexibility, flexibility in hiring and firing, benefits, etc - and it is not clear a priori which aspects really matter. In this paper, we analyse how crosscountry differences in labour market characteristics - in particular, wage and employment rigidities - shape the response of different countries to a variety of macroeconomic shocks. To address this question, we use a calibrated small open economy model in which we set the parameters governing the structural characteristics of the labour market based on three European countries: Estonia, Finland and Spain. We found that, given our labour market calibrations, we would expect output and unemployment to be much more adversely affected by the shocks associated with the financial crisis in countries with high unemployment benefit replacement ratios and high job turnover rates.
Keywords: E24; 330; Labour market structure; Labour market flexibility